VITAMIN DEFICIENCY EXPERT SYSTEM APPLICATION USING MS VISUAL FOXPRO 9.0 - Henri Saputra; Ire Puspawardani, SKom, MMSI (Jurnal Sistem Informasi, 2010)
Scientific Writing this, discussing about how to create an expert system application using Ms Visual FoxPro 9.0. Expert systems can be interpreted as a computer software which has a base of knowledge for specific domains and uses inference reasoning resembles an expert in memecahakan a problem. Where an expert system if it is related to the ability to diagnose early doctors in the patient's health condition, can be created by a computer system that served to identify and analyze patients' symptoms and then provide a direct instigation of such pesien. Scientific writing is also discussed on how to create a model of expert systems (in particular vitamin deficiency). Models made in expert system implemented in an application program. This application was made aiming to assist us in diagnosing early vitamin deficiency. And to make it easier to serve our patients without the patient must leave the house, which in addition to consuming time, effort and cost but also very concerned about his patient's condition. With this program can reduce the duty of a doctor and are not directly replace the absence of a doctor.